If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 210 = 4 * 9 * 5 + 2 * 5H Multiply 4 * 9 210 = 36 * 5 + 2 * 5H Multiply 36 * 5 210 = 180 + 2 * 5H Multiply 2 * 5 210 = 180 + 10H Solving 210 = 180 + 10H Solving for variable 'H'. Move all terms containing H to the left, all other terms to the right. Add '-10H' to each side of the equation. 210 + -10H = 180 + 10H + -10H Combine like terms: 10H + -10H = 0 210 + -10H = 180 + 0 210 + -10H = 180 Add '-210' to each side of the equation. 210 + -210 + -10H = 180 + -210 Combine like terms: 210 + -210 = 0 0 + -10H = 180 + -210 -10H = 180 + -210 Combine like terms: 180 + -210 = -30 -10H = -30 Divide each side by '-10'. H = 3 Simplifying H = 3
| x^2-11x+82=0 | | 2x+3=5x-5/3 | | y+x=r | | 2(x+9)=3(x-3) | | 78=2x-12 | | 9=y+c | | 20+b=a | | 4/3=x+2/8 | | 5w+6=16w-3w+54 | | 9y-14=6y-2 | | -3w+11=-8w+51 | | y=7x^2-4x | | 7x-5y-10=0 | | 24=-11y-8+3y | | 60*0.2= | | 3w-4=-16 | | -32=w/5-7 | | -v+131=180 | | 31=-u+184 | | 205=96-y | | -25=4u+3 | | 82-(4-6)2= | | 25n^8-49n^7-2n^6=0 | | -3+w=-4 | | -6=u-4 | | 5(2x-9)+3x=4x-18 | | 13=0.5((4x-10)+(3x+8)) | | 9x-(x+4)=2x+32 | | (1/7(x))+((1/7)x+1)+29=x | | 2x^1/2-7x^1/4+3=0 | | 63=.5h*9 | | 4x+7=54 |